2019
DOI: 10.2147/ott.s205803
|View full text |Cite
|
Sign up to set email alerts
|

<p>Bio-physic constraint model using spatial registration of delta 18F-fluorodeoxyglucose positron emission tomography/computed tomography images for predicting radiation pneumonitis in esophageal squamous cell carcinoma patients receiving neoadjuvant chemoradiation</p>

Abstract: Purpose This study integrated clinical outcomes and radiomics of advanced thoracic esophageal squamous cell carcinoma patients receiving neoadjuvant concurrent chemoradiotherapy (NACCRT) to establish a novel constraint model for predicting radiation pneumonitis (RP). Patients and methods We conducted a retrospective review for thoracic advanced esophageal cancer patients who received NACCRT. From 2013 to 2018, 89 patients were eligible for review. Staging workup and res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Nevertheless, further evaluation needs to be carried out in translating such research into clinical practice because most literature in the field had a multi-localization/multi-type tumor cohort design. Deltaradiomics features (Delta-RFs) which capture therapy-induced changes in radiomics features are now being evaluated as a complement to Response Evaluation Criteria in Solid Tumor (RECIST) criteria for monitoring therapeutic response in several tumor types (25)(26)(27)(28)(29)(30)(31). Khorrami et al showed preliminary evidence for clinical use of Delta-radiomics calculated from contrast-enhanced CT images as predictive biomarkers of response to ICIs therapy in NSCLC (31).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, further evaluation needs to be carried out in translating such research into clinical practice because most literature in the field had a multi-localization/multi-type tumor cohort design. Deltaradiomics features (Delta-RFs) which capture therapy-induced changes in radiomics features are now being evaluated as a complement to Response Evaluation Criteria in Solid Tumor (RECIST) criteria for monitoring therapeutic response in several tumor types (25)(26)(27)(28)(29)(30)(31). Khorrami et al showed preliminary evidence for clinical use of Delta-radiomics calculated from contrast-enhanced CT images as predictive biomarkers of response to ICIs therapy in NSCLC (31).…”
Section: Introductionmentioning
confidence: 99%
“…Delta radiomics reveals the difference in radiomics parameters before and after treatment, thus providing dynamic changes in radiomics during therapy. The role of delta radiomics has been investigated in a variety of diseases, such as pancreatic cancer, rectal cancer, high-grade osteosarcoma, and esophageal squamous cell carcinoma (32)(33)(34)(35). However, delta radiomics is rarely used for GC, except for one.…”
Section: Discussionmentioning
confidence: 99%
“…This concept has been accepted in similar clinical scenarios, including in neoadjuvant CCRT for rectal and esophageal cancer. 17,34…”
Section: Discussionmentioning
confidence: 99%
“…This concept has been accepted in similar clinical scenarios, including in neoadjuvant CCRT for rectal and esophageal cancer. 17,34 Concurrent cisplatin is the preferred chemotherapy regimen used in definitive CCRT for LAHC with survival benefit. 35 Additional or alternative regimens may have stronger radiosensitizing or antitumor effects, but the trade-off can be more severe toxicity.…”
Section: Discussionmentioning
confidence: 99%